Aumento excesivo de peso en el embarazo: ¿predictor de diabetes mellitus gestacional? - Condori Huaraka, Vanezza (2016)
Mr. Editor: Gestational diabetes mellitus (GDM) is one of the complications of pregnancy is defined as glucose intolerance with onset or first recognition during the second or third trimester of pregnancy (1,2). According to the epidemiological bulletin on surveillance of diabetes in Peru, in 2013 it was reported that 1.0% of all diabetes cases corresponded to DMG (3), higher than the 2012 figure was 0.7% (4).